KEARIFAN LOKAL MASYARAKAT DALAM MELESTARIKAN BATANG AIE LUNANG DI KENAGARIAN LUNANG KECAMATAN LUNANG KABUPATEN PESISIR SELATAN (JURNAL SPASIAL, 2015)
This research aim to get information or data and analyse exhaustively about local wisdom of society in preserve bar of aie Lunang in Kenagarian Lunang District Of Lunang Sub-Province Coastal area of South. Result of research show 1) Knowledge of society about is important of him continuity of bar region of aie to life seen from willingness for bertanggungjawab about continuity of bar of aie in the form of prohibition order catching fish with fish poison and also do not impinge assumed order oppose against norm and value around bar of aie and also the existence of dubious to all breaking of the rule 2) Understanding of society about local wisdom in taking care of bar region of aie very is needed, because bar of aie represent one of the very natural resources many its function to life 3) Habit of regional society of bar of aie pertained goodness and still hold gentleman's agreement firmness and norm going into effect seen from habit of society which do not use fish poison to catch fish, [do] not throw away garbage around bar of aie, using clothes which appropriately when bath in bar of aie and 4) Confidence of society that bar of aie the necessary for life of them and if impinging norm and order going into effect they believe the existence of dubious and debacle to which impinge it.Keyword: local wisdom, Society